Kontradiksi Makna Simbolik Warna Hitam dan Putih (Refleksi Kajian al-Qur'an dengan Pendekatan Semiotika) - Almunawar, Abdul Wahab; Syafruddin, Syafruddin; Zulheldi, Zulheldi; Ilhamni, Ilhamni; Faizin, Faizin (Al-Ashri: Ilmu-Ilmu Keislaman, 2024)
This article discusses the contradiction in the symbolic meaning of black and white in the Quran, whose meaning is then studied through a semiotic approach. Semiotics as an approach to studying the Quran attempts to construct the meaning of the language of the Quran using a sign system. The method of interpreting signs is to synergize the signified and the signified so as to give birth to a new meaning representation. The results of this research show that in this research the author focused the research by analyzing the symbolic meaning of black and white in the Quran using a qualitative method that is library research, namely by analyzing the content to get conclusions using the maudhu'i interpretation methodology and assisted by an approach. semiotics. In the results, the author finds symbolic meanings that contradict each other. Data sources are taken from books, books, writings related to the study of the Quran and interpretation. The results of the analysis show that black is found seven times and white 12 times in verses of the Quran which represent many meanings. In the analysis, black and white have five contradictory meanings. The contradictions in symbolic meaning that result from these symbolic meanings are, first, black is a symbol of the state of the residents of hell, while white is a symbol of the state of residents of heaven. Second, black is a symbol of night, while white is a symbol of morning. Third, black is a symbol of weakness, damage and something trivial, while white is a symbol of strength, greatness and miracles. Fourth, black is a symbol of the facial expression of a sinner, while white is a symbol of a pious person's facial expression and fifth, black and white are a symbol of interpreting the phenomenon on the mountain.